2019
DOI: 10.1101/2019.12.13.876268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BACH family members regulate angiogenesis and lymphangiogenesis by modulating VEGFC expression

Abstract: Angiogenesis and lymphangiogenesis are key processes during embryogenesis as well as under physiological and pathological conditions. Vascular endothelial growth factor C (VEGFC), the ligand for both VEGFR2 and VEGFR3, is a central lymphangiogenic regulator that also drives angiogenesis. Here we report that members of the highly conserved BACH (BTB and CNC homology) family of transcription factors regulate VEGFC expression, through direct binding to its promoter. Accordingly, downregulation of bach2a hinders b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 103 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…Cell-cycle arrest in dorsal PCV ECs is VegfC/VegfR3 dependent During embryonic development, venous and lymphatic ECs sprout from the CV in response to Vegfc-Vegfr3 signaling (Petrova and Koh, 2018;Semo et al, 2016). In zebrafish, Vegfc is ex-pressed in the hypochord and the DA (Cohen et al, 2020;Covassin et al, 2006;Hogan et al, 2009b), whereas its receptor, Flt4, is expressed in PCV ECs, including those in lymphatic and venous sprouts. Mutations in either vegfc or flt4 lead to a block in sprouting of lymphatic and venous ECs from the PCV and a failure to develop a functional lymphatic system, along with defective arteriovenous remodeling of ISVs (Covassin et al, 2006;van Impel et al, 2014;Siekmann and Lawson, 2007).…”
Section: Ecs Sprout From the Pcv In G1 Phasementioning
confidence: 99%
“…Cell-cycle arrest in dorsal PCV ECs is VegfC/VegfR3 dependent During embryonic development, venous and lymphatic ECs sprout from the CV in response to Vegfc-Vegfr3 signaling (Petrova and Koh, 2018;Semo et al, 2016). In zebrafish, Vegfc is ex-pressed in the hypochord and the DA (Cohen et al, 2020;Covassin et al, 2006;Hogan et al, 2009b), whereas its receptor, Flt4, is expressed in PCV ECs, including those in lymphatic and venous sprouts. Mutations in either vegfc or flt4 lead to a block in sprouting of lymphatic and venous ECs from the PCV and a failure to develop a functional lymphatic system, along with defective arteriovenous remodeling of ISVs (Covassin et al, 2006;van Impel et al, 2014;Siekmann and Lawson, 2007).…”
Section: Ecs Sprout From the Pcv In G1 Phasementioning
confidence: 99%
“…In parallel to indirect regulation of Vegfc by SOX7, our study identified putative VEGFC silencing elements in both the human and mouse genomes, and suggest that SOX7 can regulate Vegfc transcription through direct binding at these sites. While a handful of factors have been shown to transcriptionally regulate VEGFC expression in the past (Cohen et al, 2020; Gauvrit et al, 2018; Schuermann et al, 2015), this is the first identification of an endothelial-specific and direct molecular mechanism able to regulate Vegfc transcription.…”
Section: Discussionmentioning
confidence: 85%
“…To date, only a handful of factors have been shown to transcriptionally regulate VEGFC expression (Cohen et al, 2020; Gauvrit et al, 2018; Schuermann et al, 2015), with no previous study describing an endothelial-specific and direct molecular mechanism that regulates VEGFC transcription. Our work sheds light into how the BEC-specific SOX7 transcription factor dampens local VEGFC levels to modulate tissue growth in a paracrine manner likely via a combination of mechanisms: 1) indirectly through recruitment and transcriptional control of the repressor protein HEY1 2) directly via binding to silencing elements associated with the Vegfc locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a plethora of information on the mode of action, maturation process, and signaling mechanisms of VEGFC, there is a lack of understanding of how this growth factor is transcriptionally regulated, especially in the endothelial compartment. While the hematopoietically expressed homeobox (HHEX) genetic pathway has been implicated as an endothelial-specific regulator upstream of VEGFC expression, only the BTB and CNC homology (BACH) family of transcription factors have been shown to directly transactivate the VEGFC promoter and these experiments were performed in human ovarian carcinoma ES2 cells (Schuermann et al, 2015;Gauvrit et al, 2018;Cohen et al, 2020). Thus, there is still a paucity of information on the molecular mechanisms that drive Vegfc transcription in the endothelial cell context, despite the fact that it is well-established that endothelial-derived VEGFC is critical for blood vessel angiogenesis and coronary artery formation (Cao et al, 1998;Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%